Actitudes hacia la inclusión educativa en profesoras de primaria de instituciones privadas de educación básica regular de Lima Metropolitana - Meneses Bustios, Ximena (2016)
The present investigation has as purpose to describe attitudes toward inclusive education for people with disabilities in the primary teachers of private schools from Regular Basic Education (RBE) of Lima Metropolitana. Due to the shortage of instruments created and adapted in Lima Metropolitana, was built the Scale of Attitudes of Teachers toward Inclusive education (SATI). As a second purpose of research, we estimated the psychometric properties of the scale from its application in a sample of 280 primary school teachers of 17 private schools of RBE. The results allowed to interpret that the primary school teachers of private schools of RBE of Lima Metropolitana presented ambivalent attitudes toward inclusive education, being the teachers with prior experience who have a more positive attitude. Finally, it was concluded that the interpretations and decisions to be taken on the basis of the scores obtained from the application of the SATI presented validity and reliability evidence for primary school teachers of private schools of RBE in Lima Metropolitana.